Recent progress in heteroatom doped carbon based electrocatalysts for oxygen reduction reaction in anion exchange membrane fuel cells. (29th January 2023) - Gutru, Rambabu; Turtayeva, Zarina; Xu, Feina; Maranzana, Gaël; Thimmappa, Ravikumar; Mamlouk, Mohamed; Desforges, Alexandre; Vigolo, Brigitte
Abstract: Oxygen reduction reaction (ORR) is a key step in many electrochemical devices such as fuel cells and metal-air batteries. However, the reaction proceeds at a significant overpotential requiring Pt-based catalysts. The scarcity and economical challenges associated with Pt is one of the major limitations for the commercialization of the devices. In this context, the electrochemical research community is constantly exploring other low-cost and earth-abundant materials as ORR catalysts. Carbon nanomaterials are identified as promising electrocatalysts due to their superb electronic conductivity together with high specific surface area. However, the low reactivity of carbon is the major limiting factor in the fabrication of ORR catalysts. Recent studies have proved that chemical modification of the carbon network (substitution of foreign atoms, Ex: N, S, B, F, P) could alter the reactivity of carbon nanomaterials for ORR. Many doping strategies have been proposed including single atom doping, co-doping and multi-atom doping. The heteroatom doped carbons have delivered promising results towards ORR in alkaline media. This review presents a rational approach of doping methods and the electrochemical properties of heteroatom doped carbons, and we believe that this review could be a guiding material to design advanced non-noble catalysts for ORR in the coming future. Graphical abstract: Image 1 Highlights: Overview of oxygen reduction reaction principle and mechanism. Design and development of heteroatom doped carbon based electrocatalysts. Half-cell studies of various heteroatom doped electrocatalysts. AEMFC performance of heteroatom doped carbon catalysts. Overview on the stability of heteroatom doped electrocatalysts.